Hoping for a new dawn: a printing business / Salwa Abu Bakar … [et al.] - Abu Bakar, Salwa; A. Halid @ Khalid, Rozieana; M. Habib Rahman, Azman Ali; Ab Rashid, Mohd Elfee (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
Firdaus, the Managing Director at X-Factor Printing, strives to pick up his market share from a significant slump due to price war and digitalization transformation surrounding almost every industry. The business was incorporated in 2009 and further expanded to specialize in textile printing in 2012. At the time of the case, businesses worldwide suddenly found themselves facing much uncertainty as Covid-19 disrupts global supply chains. Firdaus is facing a decision as to whether switching from his passion for printing into something that may be more promising or look for angles where he can surpass the external pressure from an increasingly saturated industry. Specifically, he wanted to develop a sustainable strategy to align with his long-term success.